PS4:79 Long-term follow-up of 320 chilren born to mothers with systemic autoimmune diseases: a multicentre survey from 24 rheumatology centres in italy. (21st March 2018) - Lazzaroni, MG; Nalli, C; Andreoli, L; Carini, C; Dall'Ara, F; Rodrigues, M; Bartoloni Bocci, E; Gerli, R; Chighizola, CB; Gerosa, M; Meroni, PL; Sinigaglia, L; et al.
Abstract : Background: Rheumatic Diseases (RD) frequently affect women during reproductive age, therefore counselling on family planning is crucial for their quality of life. Children's outcome is a major topic, but no large studies are available. This study aimed at assessing the long-term health conditions of children born to women with RD. Methods: 24 Italian Rheumatology Centres distributed the questionnaire (65 multiple-choice and 12 open-answer questions) to consecutive patients (aged 18–55) during September 2015. Data were analysed dividing children upon maternal diagnosis: Chronic Arthritides (CA) and Connective Tissue Diseases (CTD). Results: Data were collected for 320 children born to 184 mothers (63 CA and 121 CTD). At the time of interview, children had a mean age of 17.1±9.6 years. Pre-term delivery (<37 w) was observed in 72 cases (22.5%), including 13 (4%) cases born <34 w. The occurrence of an autoimmune/inflammatory disease (AIID) and/or neurodevelopmental disorders (ND)/learning disabilities (LD) is reported in table 1. Twelve children (3.7%) were diagnosed with an AIID, mostly coeliac disease (8/12, 67%). Eleven children (3.4%) were diagnosed as having a ND and/or LD by a Paediatric Neuropsychiatrist. Data of in utero exposure to maternal autoantibodies and/or anti-rheumatic drugs were retrieved for 280 children (87.5%) and a comparison was performed between affected (n=11) and not-affected children (n=258). No association was found with ND/LD and in utero exposure to autoantibodies (ANA, anti-Ro, anti-dsDNA, aPL) or drugs (HCQ, AZA or steroids), neither with sex, preterm birth, birth weight or maternal diagnosis. Conclusions: The long-term follow-up of children born to mothers with RD did not raise particular concerns in terms of relevant health problems. In particular, each AIID did not display a significantly increased frequency as compared to the literature. Children with ND/LD had a tendency to cluster in the group of mothers with CTD, especially after maternal diagnosis, with a higher frequency as compared to GPP (7.9% vs 3%). Our data suggest that the development of ND/LD in children of patients with RD cannot be linked exclusively to maternal disease. The results of this study can be reassuring for patients with RD about problems in the offspring possibly related to their disease.